양안 외직근후전술 후 재발한 간헐외사시에서 양안 내직근절제술의 효과 - 정새롬(Sae Rom Chung); 이태은(Tae Eun Lee); 유인천(In Cheon You); 조남천(Nam Chun Cho); 안 민(Min Ahn) (Daihan angwa haghoi jabji, 2018)
목적: 간헐외사시로 양안 외직근후전술을 받은 후 재발한 환자에서 양안 내직근절제술의 효과를 알아본다. 대상과 방법: 2009년 1월부터 2015년 8월까지 간헐외사시로 외직근후전술을 받은 후 20프리즘디옵터(prism diopters, PD) 이상 외사시가 재발한 환자 중 양안 내직근절제술을 시행한 25명을 대상으로 의무기록을 후향적으로 조사하였다. 내직근절제는 원거리 사시각을 기준으로 4.0-6.5 mm까지 0.5 mm 단위로 시행하였고 수술 후 경과관찰은 1일, 1주일, 3개월, 6개월, 1년에 사시각을 측정하여 내직근절제량에 따른 사시각 교정 정도를 조사하였다. 결과: 재수술 전 사시각은 27.20 ± 5.02 PD의 외편위였고, 재수술 시 시행한 양안 내직근절제술의 양은 평균 5.10 ± 0.79 mm였다. 재수술 후 원거리 사시각은 수술 직후 10.68 ± 5.50 PD 내편위각을 보이다 시간이 지남에 따라 과교정된 내편위각이 줄어들고 수술 1년 후에는 1.16 ± 7.54 PD의 내편위각을 보였다. 수술 직후에는 84%에서 과교정 소견을 보였으나 1년이 지난 후에는 24%로 줄어들었고 수술 성공률은 68%였다. mm당 교정량은 재수술 후 1일, 1주일, 3개월, 6개월, 1년에서 각각 7.53 ± 1.22, 7.75 ± 2.16, 6.27 ± 1.74, 5.50 ± 1.54, 5.56 ± 1.58 PD/mm였으며, 시간이 지남에 따라 교정 효과가 감소하는 경향을 보였다. 수술 1년째 mm당 교정량은 내직근 절제량과 관계없이 일정하게 유지되었다(p=0.939). 결론: 양안 외직근후전술 후 20 PD 이상 재발한 외사시에서 양안 내직근절제술 시 처음에는 과교정되나 시간이 경과함에 따라 수술 후 1년에는 1.16 ± 7.54 PD 내편위각으로 정위에 가까운 소견을 보인다. 20 PD 이상의 외사시에서 양안 내직근절제술은 유용한 수술 방법이다. Purpose: The purpose of this study was to investigate the effect of bilateral medial rectus muscle resection on the treatment of recurrent intermittent exotropia. Methods: A retrospective chart analysis was conducted for 25 patients who underwent bilateral medial rectus resection for recurrent exotropia over 20 prism diopters (PD) between January 2009 and August 2015. The medial rectus was resected from 4.0 to 6.5 mm by 0.5 mm according to the deviation angle. The postoperative angle of deviation was checked at 1 day, 1 week, 3 months, 6 months, and 1 year postoperatively to investigate the amount of corrected deviation per resected muscle. Results: The average preoperative deviation angle was 27.20 ± 5.02 PD exodeviation and the mean resection was 5.10 ± 0.79 mm of the medial rectus. The postoperative angle deviation was 10.68 ± 5.50 PD esodeviation at 1 day. The incidence of esodeviation tended to decrease over time. At 1 year, the postoperative angle deviation was 1.16 ± 7.54 PD esodeviation. The overcorrection rate was 84% at 1 day postoperatively but decreased to 24% at 1 year with a success rate of 68%. The corrected deviation angle per millimeter was 7.53 ± 1.22, 7.75 ± 2.16, 6.27 ± 1.74, 5.50 ± 1.54, and 5.56 ± 1.58 PD/mm at 1 day, 1 week, 3 months, 6 months, and 1 year after surgery, respectively. The dose effect per millimeter decreased over time. The corrected deviated angle per millimeter remained constant regardless of the amount of medial rectus muscle resection at 1 year postoperatively(p=0.939). Conclusions: Bilateral medial rectus resection for recurrent exotropia over 20 PD tended to overcorrect at first; however, after 1 year, the mean angle of deviation was 1.16 ± 7.54 PD esodeviation. Bilateral medial rectus resection is an effective surgical method for the treatment of recurrent exotropia over 20 PD. KCI Citation Count: 1